Results Multi-Laboratory Trial ISO/CD 22184—IDF/WD 244: Milk and Milk Products—Determination of the Sugar Contents—High-Performance Anion Exchange Chromatography Method with Pulsed Amperometric Detection. (21st July 2020) - Brunt, Kommer; Sanders, Peter; Ernste-Nota, Veronica; van Soest, J.
Abstract: Background: In this international Multi-Laboratory Trial (MLT) the precision data and the accuracy of the ISO/CD 22184 IDF/WD 244 analytical method for the quantification of 6 different mono- and disaccharides (galactose, glucose, fructose, sucrose, lactose, and maltose) in milk and milk products with high-performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) are established. Objective: Thirteen different laboratories participated (located in New Zealand, the United States, and Europe). The study was divided into two parts. First, the learning/familiarization part in which the participants got experienced with the method. After successfully completing this part, the participants were allowed to continue with the second part of this trial: the analyses of the seven blind MLT duplicate samples. Method: The selected seven MLT samples comprise five MUVA reference dairy samples, one NIST-certified infant formula and one industrial sample. In the Tables S-1 to S-6 the results of this MLT study have been summarized per sugar. There is a very good agreement between the MUVA and NIST-certified sugar contents in the MLT samples and in the MLT established sugar contents in those MUVA and NIST samples. Results: This demonstrates that the accuracy of the newly developed HPAEC-PAD method is very good. Conclusions: Certificates of analysis were available for both the MUVA samples and the NIST sample. There is a very good agreement between the by MUVA- and NIS-certified sugar contents in the MLT samples and the corresponding in the MLT established sugar contents. This demonstrates that the accuracy of the HPAEC-PAD method is very good. In the IDF/ISO Analytical Week in June 2019 in Prague the report on the MLT study were discussed and adopted.